(untitled) (Revista Latino-Americana de Enfermagem, 2011)
Among the methods available for assessing body composition, traditional methods like hydrodensitometry and skin-fold measurements are well known. In this review, we focus on the impedance and interactance methods, which use systems that are usually inexpensive, easily transportable and simple to operate. We also discuss the usefulness of dual energy X-ray absorptiometry, particularly for the measurement of fat distribution. Nurses need to be skilled in the use of the equipment and familiar with the techniques.